2013
DOI: 10.1148/radiol.12120707
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Susceptibility Mapping in Multiple Sclerosis

Abstract: Purpose:To apply quantitative susceptibility mapping (QSM) in the basal ganglia of patients with multiple sclerosis (MS) and relate the findings to R2* mapping with regard to the sensitivity for clinical and morphologic measures of disease severity. Materials and Methods:The local ethics committee approved this study, and all subjects gave written informed consent. Sixty-eight patients (26 with clinically isolated syndrome, 42 with relapsing-remitting MS) and 23 control subjects underwent 3-T magnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
229
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 236 publications
(246 citation statements)
references
References 40 publications
(44 reference statements)
14
229
0
3
Order By: Relevance
“…11,31-34 Our ROC and interobserver agreement results here show that QSM is more accurate than R2* mapping for measuring substantia nigra change in PD; this finding is consistent with that in a recent study showing that QSM is more accurate than R2* mapping in measuring basal ganglia change in multiple sclerosis. 23 Therefore, QSM may replace R2* mapping for MR imaging measurement of iron-associated change in the brain.…”
Section: Fig 2 R2* (Top Row)mentioning
confidence: 99%
See 1 more Smart Citation
“…11,31-34 Our ROC and interobserver agreement results here show that QSM is more accurate than R2* mapping for measuring substantia nigra change in PD; this finding is consistent with that in a recent study showing that QSM is more accurate than R2* mapping in measuring basal ganglia change in multiple sclerosis. 23 Therefore, QSM may replace R2* mapping for MR imaging measurement of iron-associated change in the brain.…”
Section: Fig 2 R2* (Top Row)mentioning
confidence: 99%
“…21,22 Clinical data from patients with multiple sclerosis suggest that QSM is more sensitive than R2* mapping in detecting changes in multiple sclerosis brains. 23 According to a previously published study using QSM, a significant difference was not found between patients with PD and healthy control subjects for the susceptibility value of the substantia nigra. 24 However, because only 9 patients were available for the previous study, the clinical potential of QSM has not been fully elucidated.…”
mentioning
confidence: 96%
“…However, iron deposition was noted in the absence of any significant volume change. In addition to R2* relaxometry, Langkammer et al 90 performed quantitative susceptibility mapping on 26 subjects with CIS. Quantitative susceptibility mapping detects magnetic charge variations attributable not only to iron, but also but also to myelin.…”
Section: Brain Iron Quantificationmentioning
confidence: 99%
“…Apparently conflicting results by these 2 recently published studies may be attributable to differences in image processing techniques. Langkammer et al 90 …”
Section: Brain Iron Quantificationmentioning
confidence: 99%
“…112,130 The presence of iron is suggestive of microglia activity, and positive signal has been associated with chronic active MS lesions. 34,[131][132][133][134][135][136][137][138][139][140][141] Longitudinal QSM studies, conducted in our center, showed that lesion susceptibility increased as the lesion evolved from contrast enhanced to nonenhanced, indicating that it could be used as a biomarker. [142][143][144] All of these advanced magnetic resonance modalities require further validation in larger cohorts of patients and over a longitudinal time span.…”
Section: Introduction Of New Mri Sequences and Future Utilizationmentioning
confidence: 99%